2015
DOI: 10.1177/0886260515604412
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Sexism, Alcohol Use, and Intimate Partner Violence Perpetration

Abstract: Research on risk factors for men's perpetration of intimate partner violence (IPV) has shown a high correlation with problem alcohol use. Additional studies, however, indicate that the alcohol-IPV link is neither simple nor necessarily direct and that a range of factors may moderate this relationship. Using a national, community-based sample of 255 men, the present study examined the moderating effects of ambivalent sexism (i.e., hostile and benevolent sexism) on the relationship between alcohol use and IPV pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 81 publications
4
42
0
2
Order By: Relevance
“…Alcohol use by men in this sample was a strong risk factor for IPV, in keeping with a large body of evidence [7,8,39]. The complex relationships and interactions between alcohol, attitudes and IPV are now coming under scrutiny in an attempt to better understand how and when alcohol use leads to IPV perpetration [40,41].…”
Section: Plos Onesupporting
confidence: 73%
“…Alcohol use by men in this sample was a strong risk factor for IPV, in keeping with a large body of evidence [7,8,39]. The complex relationships and interactions between alcohol, attitudes and IPV are now coming under scrutiny in an attempt to better understand how and when alcohol use leads to IPV perpetration [40,41].…”
Section: Plos Onesupporting
confidence: 73%
“…Allen, Swan, and Raghavan (2009) reviewed existing studies examining the links between sexist attitudes, including hostile and benevolent sexism scales- Spence and Helmreich's (1972) Attitudes Toward Women Scale and Glick and Fiske's (1996) Ambivalent Sexism Inventory-, and IPV usually assessed via behavioral self-reports (e.g., Conflict Tactic Scale 2 -CTS, Straus, Hamby, Boney-McCoy, & Sugarman, 1996). Their review suggested that sexist attitudes toward women were not consistently related to IPV against women (see also Cross et al, 2017;Herrero, Torres, Rodríguez-Díaz, & Juarros-Basterretxea, 2017; Juarros-Basterretxea, Renzetti, Lynch, & DeWall, 2015). Allen et al (2009) pointed out that the relation between sexism and IPV is more consistent when examining hostile sexism, whereas the association between benevolent sexism and IPV is inconsistent perhaps because benevolent sexism promotes protection of women who adhere to gender roles, but more punishing attitudes toward women who violate gender roles (Glick, Sakalli-Ugurlu, Ferreira, & Aguiar de Souza, 2002).…”
Section: Sexist Attitudes Acceptance Of Ipv and Ipv Perpetrationmentioning
confidence: 99%
“…One of these explanatory indicators is adolescents' degree of acceptance of violence, although this indicator is generally linked to exposure to previous abusive situations within the family context or to a history of abuse suffered [14,15]. Sexist attitudes have also been associated with the phenomenon of dating violence, fundamentally in a descriptive way [40,41], or with other factors such as alcohol consumption [42]. The interest of the present study is that the role of protagonist is given to the victim, and that its analysis of the factors which contribute to sustaining the role of victim is multidimensional and interrelated.…”
Section: Introductionmentioning
confidence: 99%